Study on the in-situ modified support method of roadway surrounding rock under vertical impact load - Heng Zhang; Su Liu; HaiYang Yi; Juntong Liu; Yan Qin; Yuqian Li; Yan Dong; Yong Cao; Fangchao Lu; Shaoshuai Guo; Tie Li; Yan Liu (Scientific Reports)
Abstract With the deepening of coal mining, the frequency and intensity of rock burst accidents are increasing. According to incomplete statistics, there have been over 200 rock burst accidents in tunnels in China alone from 2005 to 2024, resulting in more than 500 deaths and causing extensive damage to tunnel equipment. Therefore, research on tunnel surrounding rock support methods is urgently needed. Based on a large number of previous studies on the surrounding rock support methods and technologies of coal mine roadway, this paper innovatively proposed the in-situ modified support method of roadway surrounding rock, and compared and analyzed the differences between the original rock roadway and the in-situ modified roadway surrounding rock in terms of static stress redistribution, displacement, plastic zone, dynamic stress and kinetic energy dissipation by using numerical simulation and laboratory experiments. The results show that the surrounding rock in the cracked region and reinforced region can redistribute the static stress of the roadway, better transfer the high static stress concentration distribution zone to the outside of the surrounding rock in the cracked region, and the dynamic stress transmitted to the surrounding rock surface of the roadway is reduced by about 1.29 ~ 4.0 times. Under the action of large vertical dynamic load, the displacement of surrounding rock in the roadway reinforcement area is reduced by about 1.9 ~ 4.0 times, the dynamic stress is reduced by about 37%~48%, and the overall plastic zone is significantly reduced. The plastic failure of coal and rock in the cracked region consumes and weakens the impact energy, enhances the dissipation effect of kinetic energy in surrounding rock, and effectively ensures the integrity of coal and rock in the reinforced region. The above research results can provide new support theory and technical ideas for surrounding rock support of roadways prone to rock bursts, prevent roadway rock burst accidents, and ensure mine safety production.